Kid Crop Goat Kacang in West Muna District, Southeast Sulawesi - ZulZalima, Wa Ode; Aka, Rahim; Rahman, Rahman (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
Kid crop is a value used to express the number of children born to weaning age from the parent population that gives birth in one period. This study aims to determine the value of the kid crop of Kacang goats in Muna Barat Regency using the stratified sampling method with the research area covering 3 districts including Kusambi, Sawerigadi, Wadaga Subdistricts, and determining the selected respondents using the Purposive Sampling method with the research material being goats with 92 parents. tails that have a minimum requirement of having given birth 2 times. The results showed that the average value of the kid crop of Kacang goats in West Muna Regency was 143.45% with an interval of 8.29 months and the number of children born was 2.04, while the cempe mortality rate reached 16.72%%.